IDENTIFICATION OF DRUG-RELATED PROBLEMS IN ADULTS WITH TUBERCULOSIS AT THE TEBET SUBDISTRICT HEALTH CENTER FROM JULY TO DECEMBER 2018 - PUSPITASARI, ATIKA WAHYU; YUNAZ, SAVIRA RAHMAWATI; NADHILAH, LINA (International Journal of Applied Pharmaceutics, 2020)
Objective: Tuberculosis (TB) is a highly prevalent infectious disease caused by Mycobacterium tuberculosis. The recommended TB treatment is a combination of various antibiotics in the form of a fixed-dose combination tablet or kombipak; however, this increases the prevalence of drug-related problems. Therefore, this study aimed to identify drug-related problems of patients receiving TB therapy at the Tebet Subdistrict Health Center from July 2018 to December 2018. Methods: The study was designed as a cross-sectional study using the retrospective data retrieval method from prescriptions of patients with TB from July 2018 to December 2018. The classification system prepared by Cipolle, Strand, and Morley was used for the classification of drugrelated problems; this system includes unnecessary drug therapy, required additional drug therapy, ineffective drug, dosage error, and drug interaction. Results: The percentage of unnecessary drug therapy, required additional drug therapy, ineffective drug, dosage error, and drug interaction was 2.85%, 6.89%, 1.54%, 12.46%, and 66.18%, respectively, with the occurrence of drug-related problems being the highest. Conclusion: The administration of anti-TB drugs can potentially cause drug-related problems. Therefore, the assessment needs to be optimized before the administration of medications to patients and medications should be prescribed and monitored regularly to achieve rational drug use